Peranan Komunikasi Visual bagi Identitas Perusahaan - Luzar, Laura Christina; Monica, Monica (Humaniora, 2013)
In the current era of globalization, along with expanding the market, many companies are competing to attract the attention of consumers to buy their products. One way to compete and survive in this growing market is by creating an image and visual identity. Strong characters could position the image of a company, visual identity is so necessary in showing the image which wants to be introduced to the public. The vigorous competition between firms creates visual identity, become a prominent feature of each companies. Therefore, it is needed a visual communication designer who can create and develop the concept of corporate identity systems. Visual communication designer also have responsibility to create identity into a system that does not sell directly, but provides identity, information, persuasive and ultimately serves as an effective marketing media.